MMN BASED COLLABORATIVE FILTERING APPROACH FOR SELECTION OF LOCATION AWARE SERVICES - Sushmitha, S; Kavitha, J.C (IJRDO -Journal of Computer Science Engineering, 2015)
Web services are a method of communication between two electronic devices over a network. The number of web services which are publicly available is increasing steadily on the internet which makes it difficult for the users to select a proper web service. Additional overhead in time and resources takes place when the developers are not able to select a proper web service. Therefore, effective approaches to service selection and recommendation are in an urgent need. Also using the same QoS values for all the users will not give a good recommendation for the user. In the proposed system, personalized QoS prediction is provided so that for each user the QoS values will be calculated and the best recommended web service is provided. A collaborative filtering based web service recommender system is used to help users select a quality web service. Using the location information and QoS values, the services are normalized using MMN based collaborative filtering approach and then it is ranked to give the best web service recommendation for users.